2023
DOI: 10.1212/wnl.0000000000207812
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Duration of Breastfeeding in the Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs Study

Elizabeth E. Gerard,
Kimford J. Meador,
Chelsea P. Robalino
et al.

Abstract: Background and Objectives: Breastfeeding has important health benefits for both mother and child. We characterize breastfeeding initiation and duration in mothers with epilepsy relative to control mothers in a large prospective cohort. Methods: The Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is a prospective, multi-center observational, US cohort study. Pregnant subjects with and without epilepsy, aged 14-45, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Three cases of sedation were reported among 16 children breastfed by mothers taking levetiracetam, which resolved shortly after switching to partial breastfeeding [45]. A large prospective study, of which 84 breastfeeding women were on levetiracetam, did not show overall adverse effects at age two years across all ASMs [46].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Three cases of sedation were reported among 16 children breastfed by mothers taking levetiracetam, which resolved shortly after switching to partial breastfeeding [45]. A large prospective study, of which 84 breastfeeding women were on levetiracetam, did not show overall adverse effects at age two years across all ASMs [46].…”
Section: Resultsmentioning
confidence: 95%
“…Prospective long‐term follow‐up studies of developmental outcomes among children that have been breastfed by mothers taking ASMs are sparse [15-17, 46], and have mainly involved children whose mothers were taking carbamazepine, lamotrigine, levetiracetam, phenytoin or valproate while breastfeeding. None of these studies indicated poorer outcome among breastfed children compared with those who were not breastfed [15-17, 46]. In fact, among children of mothers treated with valproate, IQ at six years of age was higher in those who had been breastfed compared to those who had not [16].…”
Section: Summary and General Comments On Reported Data In Relation To...mentioning
confidence: 99%